Proceedings of the 8th Annual International Conference on Mobile Computing and Networking 2002
DOI: 10.1145/570645.570656
|View full text |Cite
|
Sign up to set email alerts
|

A transport layer approach for achieving aggregate bandwidths on multi-homed mobile hosts

Abstract: Due to the availability of a wide variety of wireless access technologies, a mobile host can potentially have subscriptions and access to more than one wireless network at a given time. In this paper, we consider such a multi-homed mobile host, and address the problem of achieving bandwidth aggregation by striping data across the multiple interfaces of the mobile host. We show that both link layer striping approaches and application layer techniques that stripe data across multiple TCP sockets do not achieve t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
98
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 159 publications
(98 citation statements)
references
References 23 publications
(18 reference statements)
0
98
0
Order By: Relevance
“…This implies that they share real-time requirements with applications like multimedia and video services [44,46,21,16]. Figure 1 shows a prototypical, distributed collaborative visualization [1,48].…”
Section: Real-time Collaborationmentioning
confidence: 99%
“…This implies that they share real-time requirements with applications like multimedia and video services [44,46,21,16]. Figure 1 shows a prototypical, distributed collaborative visualization [1,48].…”
Section: Real-time Collaborationmentioning
confidence: 99%
“…2 While such approaches can be used for content downloads, they are not applicable to most other applications that maintain a limited buffer and require the in-sequence delivery service from lower layers. It has been shown in [9] that for such applications the performance achieved can be throttled by the slowest link in the connection if application-layer striping is performed without transport layer support.…”
Section: The Destination (Requesting Peer)mentioning
confidence: 99%
“…Out-of-order arrivals not only call for a large resequencing buffer at the receiver, but can also introduce headof-line blocking. It has been shown in [9] that head-ofline blocking can cause significant performance loss in terms of achieving the aggregate bandwidth. As we mentioned in Section 3.1, different paths in a multipoint-to-point connection can exhibit very different characteristics in terms of bandwidth/latency mismatches and fluctuations.…”
Section: Packet Schedulingmentioning
confidence: 99%
“…Recent studies have suggested that concurrent multi-path transfer (CMT) (Phatak and Goff, 2002;Hsieh and Sivakumar, 2005;Iyengar et al, 2006;Liao et al, 2008) is an effective traffic engineering technique to improve throughput by aggregation of bandwidth, especially for the high-bandwidth applications such as video sharing/download/streaming. Other benefits include increased service reliability, latency reduction, and fault tolerance by sending redundant data over different paths, and enhanced mobility when combining coverage areas of multiple mobile and wireless access networks.…”
Section: Introductionmentioning
confidence: 99%